Lipid distributions associated with cadaver decomposition in mangrove and oil palm plantation soils under tropical climate = Taburan lipid berkaitan dengan pereputan kadaver dalam tanah bakau dan ladang kelapa sawit di bawah iklim tropika - Ismail, Siti Sofo; Xueer, Chock; Kholidan, Mohamad Afdhali; Ku Yusof, Ku Mohd. Kalkausar; Jemain, Siti Fathimah Putery (Malaysian Analytical Sciences Society (ANALIS), 2020)
The burial environment has a significant effect on decomposition process. The most influential environmental factors that determine the fate of the process are temperature, moisture, pH, and partial pressure of oxygen. In this study, the decomposition of a cadaver buried in soils with contrasting pH under a tropical climate was investigated. Due to ethical issues, the fatty flesh of a commercial pig (Sus scrofa) was buried in mangrove (mild alkaline pH) and oil palm plantation (acidic pH) soils, which are amongst the most common body disposal sites encountered in forensic investigations. A controlled laboratory experiment was carried out. Soils were collected at different sampling points, corresponding to different decomposition stages. Modified Bligh-Dyer extraction method was used to extract soil lipids. Gas chromatography-flame ionisation detector (GC-FID) was used to identify the obtained lipids. A similar trend in the rate of decomposition was observed for both soils. The decomposition rate was higher at the initial and putrefaction stages. A sharp increase in the decomposition rate was observed between day 3 and day 5 of the burial interval. However, mangrove soil demonstrated a higher decomposition rate at all decomposition stages. Furthermore, the concentrations of palmitic (C16:0), stearic (C18:0), and oleic (C18:1) acids were higher in mangrove soil compared to that of oil palm plantation soil. The significant differences observed between these contrasting pH soils may indicate that soil pH will eventually impose a different effect on decomposition.